ANALYSIS OF THE SOCIAL-PSYCHOLOGICAL COMPETENCIES OF A TEACHER’S PERSONALITY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This research explores the importance of social-psychological competencies in the professional development and effectiveness of teachers. These competencies, which include emotional intelligence, communication skills, empathy, and stress resilience, significantly impact teachers' ability to engage with students, manage classroom dynamics, and foster a supportive learning environment. The study highlights how teachers with developed social-psychological skills are more effective in addressing students' emotional and academic needs, creating a positive classroom atmosphere, and promoting students' personal and social development. Furthermore, it emphasizes the necessity of targeted training programs aimed at enhancing teachers' social-psychological competencies to improve their professional performance and contribute to the overall success of the educational process. The findings underscore the critical role these competencies play in shaping teachers' interactions with students and their ability to navigate the challenges of modern education effectively.